Egyptian customs and festivals - Abdennour, Samia (American University in Cairo Press, 2007)
How do Egyptian Muslims celebrate Ramadan? How do Copts Egyptian Christians celebrate Easter? What should you expect to find on the table when invited to eat in an Egyptian home? What do you say when an Egyptian colleague sneezes? Exactly what do Egyptians do with a mortar and pestle, a sieve, and a bag of nuts seven days after the birth of a baby? Samia Abdennour, once an outsider from Palestine, now thoroughly at home in Egypt, is here to tell you all about these matters and many more. In a book that aims to introduce the unfamiliar newcomer or interested foreign reader to the hows, whats, a.